Comparison on the Efficacy and Safety of Different Surgical Treatments for Benign Prostatic Hyperplasia With Volume >60 mL: A Systematic Review and Bayesian Network Meta-Analysis of Randomized Controlled Trials. Issue 6 (December 2021) - Wang, Yong-Bo; Yan, Si-Yu; Xu, Xiao-Feng; Huang, Xing; Luo, Li-Sha; Deng, Yu-Qing; Li, Xu-Hui; Huang, Qiao; Wang, Yun-Yun; Huang, Jiao; Jin, Ying-Hui; Zeng, Xian-Tao
The objective of this study was to compare the efficacy and safety of 10 different surgical treatments for benign prostatic hyperplasia (BPH) with volume >60 mL. A systematic literature review and network meta-analysis of randomized controlled trials (RCTs) within a Bayesian framework was performed. A total of 52 parallel-group RCTs included, reporting on 6, 947 participants, comparing open prostatectomy (OP), monopolar/bipolar transurethral resection of prostate (monopolar/ bipolar TURP), thulium, holmium and diode laser enucleation of prostate (LEP), bipolar enucleation of prostate, potassium titanyl phosphate laser vaporization of prostate (KTP LVP), bipolar vaporization of prostate (bipolar VP), and laparoscopic simple prostatectomy (laparoscope SP). Compared with OP, laparoscope SP identified better maximal flow rate (Qmax; mean differences [MDs] = 2.89 mL/s) at the 24th month, but bipolar VP demonstrated worse Qmax (MD = −3.20 mL/s) and International Prostate Symptom Score (IPSS; MD = 2.60) at the 12th month. Holmium LEP (MD = 1.37) demonstrated better International Index of Erectile Function–5 at the 12th month compared with OP. However, compared with OP, KTP LVP demonstrated worse postvoid residual volume (PVR) at the sixth (MD = 10.42 mL) and 12th month (MD = 5.89 mL) and monopolar TURP (MD = 6.9 mL) demonstrated worse PVR at the 12th month. Eight new surgical methods for BPH with volume >60 mL appeared to be superior in safety compared with OP and monopolar TURP due to fewer complications. Bipolar VP and KTP LVP maybe not suitable for prostates more than 60 mL due to short- and middle-term worse Qmax, IPSS, and PVR than OP.